Renal Disease: Common Causes of Admission into Adult Medical Wards of Komfo Anokye Teaching Hospital, Kumasi, Ghana (Journal of Science and Technology, 2016)
Each year, between 2-3% of the cases admitted into the adult medical wards of Komfo Anokye Teaching Hospital are due to renal diseases, Prospective analysis of 350 cases admitted over a 3-year period (1988 - 1990) shows that most of the patients (28.0%) present with chronic renal failure. There is a high mortality rate of 40.8% due to the frequency of terminal uraemia and the fact that there is no possibility of managing such patients with regular dialysis or transplantation. The patients with chronic renal failure are relatively young with mean age of 36.1 years. The incidence of Urinary tract infection is 27.40%. Pyelonephritis is 14.8% and Nephrotic Syn-drome (NS) is 14.3%. The remaining 15.5% is made up of glomerulonephritis.(9.8%) and acute renal failure and other forms of renal disease (5.7%). There is a need to control renal disease by public education. In the long term however it will be necessary to make possible for the treatment of patients in end-stage chronic renal failure with regular dialysis and transplantation in Ghana.